Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/ghg.1843
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear interval number programming algorithm for CO2 pipeline transportation design under uncertainties

Abstract: Carbon capture, utilization and storage (CCUS) technology includes three sub‐systems of CO2 capture: transportation, utilization, and storage. Pipeline transportation is the middle link of CCUS, and its optimization is closely connected with the other two sub‐systems. However, technical and economic parameter uncertainties strongly affect the optimal pipeline cost, which creates a need for flexibility in pipeline design. To solve the flexible optimization design problem in CO2 pipeline transportation, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Fu et al [15] proposed a grey target decisionmaking model of interval numbers based on positive and negative clouts aiming at the multiattribute decision-making problem with incomplete and uncertain attribute weight information and an attribute value of interval numbers. Tian et al [16] provided an interval number optimization algorithm to solve the flexible optimization design problem in CO 2 pipeline transportation. Numerical results showed that the method could solve the flexible optimization problem effectively in the presence of uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [15] proposed a grey target decisionmaking model of interval numbers based on positive and negative clouts aiming at the multiattribute decision-making problem with incomplete and uncertain attribute weight information and an attribute value of interval numbers. Tian et al [16] provided an interval number optimization algorithm to solve the flexible optimization design problem in CO 2 pipeline transportation. Numerical results showed that the method could solve the flexible optimization problem effectively in the presence of uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 capture and storage (CCS) plays an important role in controlling carbon dioxide emissions and reducing the greenhouse effect . Large‐scale CCS projects require a large amount of CO 2 to be transported . However, the formation of CO 2 hydrates becomes a major problem, affecting the safety of CO 2 pipeline transportation .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Large-scale CCS projects require a large amount of CO 2 to be transported. [9][10][11][12][13] However, the formation of CO 2 hydrates becomes a major problem, affecting the safety of CO 2 pipeline transportation. [14][15][16][17] The formation and deposition of hydrate shrinks the passageway of the airflow and reduces the transportation efficiency, and the huge volume of hydrate causes pipeline blockage and rupture accidents.…”
Section: Introductionmentioning
confidence: 99%